Analisis Penerapan Akuntabilitas Pengelolaan Dana Zakat Studi Pada Baznas Kota Makassar - Mawahib.R, Abul (SMARTINDO, 2024)
The existence of a gap between the potential of zakat and the realization of zakat collection has shown that there are problems in zakat management that need to be addressed. One of them is related to accountability. With regard to zakat institutions, accountability is a form of accountability for their duties as zakat management. Therefore, as with the demands for accountability, zakat institutions need to increase accountability because it will affect public trust. This research is a qualitative descriptive research with qualitative methods. The focus of the research includes financial accountability in the management of zakat funds. Data in the form of primary data and secondary data. Data was collected by observation, interviews and documentation. The results showed that the zakat management carried out by Makassar City BAZNAS in implementing accountability, especially in financial accountability, was quite good but not optimal. This can be seen, first from the supervisory system implemented by Makassar City BAZNAS. Supervision is carried out by the Internal Party of BAZNAS and external supervision by the Public Accounting Firm. The results of this supervision can be seen from the existence of accountable reports to interested parties. The second is the responsibility for BAZNAS's compliance with the rules and laws that have been set. The success and responsibility for these can be seen from the reports that have been audited by the Public Accounting Firm. The third is the openness of Baznas to its information to the public which needs to be maximized. This is due to media management that has not been maximized, the delay of the Makassar City BAZNAS in providing information to the public and there is still information that has not been conveyed to the public.